Merekonstruksi Kesalahan Korporasi dalam Pertanggungjawaban Pidana di Bidang Perpajakan - Profianto, Mardonius Irawan; Sugeng, Sugeng (Jurnal sosial dan sains, 2025)
This research discusses the establishment of the concept of corporate fault in the issue of criminal liability in the field of taxation in Indonesia. Specifically, this study focuses on the application of the theory of corporate criminal liability to tax offenses, with West Jakarta District Court Decision Number 334/Pid.Sus/2020/PN.Jkt BRT as the main object of analysis. This research employs a normative juridical approach with case study methodology. The research findings reveal that although the Law on General Provisions and Tax Procedures (UU KUP) does not expressly mention that corporations can be perpetrators of criminal offenses, in practice the court still applies criminal liability to corporations. This is possible due to the use of theories and doctrines in corporate criminal law, such as the doctrine of power requirements (machtsvereiste), the concept of normative guilt, and the teaching of benefits. These three doctrines have found their momentum in the new Criminal Code (Law Number 1 Year 2023), particularly in Article 48 which expressly regulates corporate criminal liability. The application of this article will officially begin on January 2, 2026, providing a clearer legal foundation for the enforcement of criminal law against corporations in the future. The main contribution of this research is to provide a deeper understanding of the principle of legality and corporate criminal liability procedures in taxation issues. Not only that, the results of this research are also important as a reference for the development of corporate criminal law in Indonesia.